Estudo termo-mecânico de interconector metálico recoberto com filme de La0,8Ca0,2CrO3 e de interconector cerâmico de La0,8Sr0,2Cr0,92Co0,08O3 para PaCOS - Sousa, Cláwsio Rogério Cruz de (2014)
Doped lanthanum chromite ( LaCrO3 ) has been the most common material used as interconnect in solid oxide fuel cells for high temperature ( SOFC-HT ) that enabling the stack of SOFCs. The reduction of the operating temperature, to around 800 º C, of solid oxide fuel cells enabled the use of metallic interconnects as an alternative to ceramic LaCrO3, From the practical point of view, to be a strong candidate for interconnect the material must have good physical and mechanical properties such as resistance to oxidizing and reducing environments, easy manufacture and appropriate thermo-mechanical properties. Thus, a study on the physic-mechanical interconnects La0,8Sr0,2Cr0,92Co0,08O3 ceramics for SOFC -AT obtained by the method of combustion , as well as thermo-mechanical properties of metallic interconnects (AISI 444) covered with La0,8Ca0,2CrO3 by deposition technique by spray-pyrolysis fuel cells for intermediate temperature (IT-SOFCs). The La0,8Sr0,2Cr0,92Co0,08O3 was characterized by X -ray diffraction(XRD) , density and porosity , Vickers hardness (HV) , the flexural strength at room temperature and 900 °C and scanning electron microscopy (SEM). The X -ray diffraction confirmed the phase formation and LaCrO3 and CoCr2O4, in order 6 GPa hardness and mechanical strength at room temperature was 62 MPa ceramic Interconnector. The coated metal interconnects La0,8Ca0,2CrO3 passed the identification by XRD after deposition of the film after the oxidation test. The oxidative behavior showed increased resistance to oxidation of the metal substrate covered by La0,8Ca0,2CrO3 In flexural strength of the coated metal substrate, it was noticed only in the increased room temperature. The a SEM analysis proved the formation of Cr2O3 and (Cr,Mn)3O4 layers on metal substrate and confirmed the stability of the ceramic La0,8 Ca0,2CrO3 film after oxidative test